Effect of deposition parameters on kinematics growth and optical properties of Fe2O3 nano films deposited by PLD - Suad Mahmood Kadhim (Journal of Madenat Alelem University College, 2019)
The optical and structural properties of Fe2O3 thin films deposited via pulsed laser deposition (PLD) have been studied. In PLD the energy of laser pulses was varied to investigate the properties of Fe2O3 thin films. In this work, different thickness of Fe2O3 thin film are deposited on glass substrates, namely, 63 nm, 110 nm and 189 nm.The structure of Fe2O3 thin films is investigated by the X-Ray diffraction, and it was formed to be polycrystalline structure. The XRD measurements show that these nano films have sharp peaks at 2θ =25º indicating a preferred orientation along (012) plane and the grain size (GS) increase with energy of laser pulses. The surface morphology of the deposited material has been tested via (SEM) gives good homogeneous films. According to the results, the nanoparticles GS and the thickness are ranging from (6.8 nm to 12.4 nm) and from (63 nm to 189 nm) is observed, respectively. The optical band gab of prepared films in range about (2.28-2.8eV)